Exploring Atmospheres Ethnographically - Schmitt, Susanne B.; Schroer, Sara Asu (London : Taylor and Francis, 2018)
"The notion of atmosphere has always been part of academic discourse, but often refers to something vague and diffuse - a phenomenon connected with our affective engagement with the world that is difficult to grasp. This volume develops and refines the concept of atmosphere, seeking to render it productive for anthropological and social scientific research by bringing together a range of original ethnographic studies in combination with investigation of the use of the term in language. The chapters examine dimensions of atmosphere through topics of interdisciplinary concern, such as learning and the acquisition of skills, the experience of place, affect and mood, multi-species relations and the perception of weather and environment - whether in natural landscapes, medical and educational settings, homes or creative contexts - Exploring Atmospheres Ethnographically analyses the relational and transformational processes through which people perceive, experience and live in a moving atmospheric world. As such, it will appeal to scholars of anthropology, sociology, geography and cultural studies with interests in space and place, sensory ethnography and affect."--Provided by publisher.
chapter 1 Introduction: thinking through atmospheres / SARA ASU SCHROER AND SUSANNE B. SCHMITT -- chapter 2 Hauptschule: atmospheres of boredom and ruination STEFAN WELLGRAF -- chapter 3 The making of pub atmospheres and George Orwell$1 (Bs Moon Under Water /s ROBERT SHAW -- chapter 4 Vapours in the sphere: malaria, atmosphere and landscape in wet lands of Agro Pontino, Italy / PAOLO GRUPPUSO -- chapter 5 Senses of being: the atmospheres of listening to birds in Britain, Australia and New Zealand / Britain, Australia and New Zealand ANDREW WHITEHOUSE -- chapter 6 (3z(BA feeling for birds(3y(B: tuning into more-than-human atmospheres /s SARA ASU SCHROER -- chapter 7 Making charismatic ecologies: aquarium atmospheres / SUSANNE B. SCHMITT -- chapter 8 Waves of experience: atmosphere and Leviathan / JULIA BEE -- chapter 9 From affective encounters to wearable forms: fashion design pedagogy and the creation of atmosphere / TODD E. NICEWONGER -- chapter 10 Living atmospheres: air, breath, song and mutual constitution in experimental theatre / CAROLINE GATT -- chapter 11 The harsh smell of scentless art: on the synaesthetic gesture of hospital atmosphere / ANETTE STENSLUND -- chapter 12 On the dynamic and duration of atmosphere: sounding out New Phenomenology through music at China$1 (Bs margins /s FRIEDLIND RIEDEL.
Keywords: Anthropology; Cultural geography; Environmental geography